Self-regulation in children with attention deficit disorders and hyperactivity a problem in child development (Revista Venezolana de Salud Pública, 2018)
Attention Deficit Hyperactivity Disorder (ADHD) is characterized by a pattern of lack of attention, hyperactivity and impulsivity; derived from poor behavioral, cognitive and emotional self-regulation that negatively impacts the patient and their environment, and that if we are treated in time can trigger behavioral, emotional and social problems such as mood disorders, antisocial behavior, substance abuse among others. To explain ADHD, Barkley (1997) points out that the key symptoms underlie a deficit in inhibitory control associated with executive dysfunctions, which impede self-regulation. The objective of the present investigation was to determine self-regulation in children with ADHD. The research was carried out through a non-experimental and transversal design. The population consisted of parents of children with ADHD between 6 and 8 years of age who attend the Psychoeducational Development Center CEDEPSI, C.A. For data collection, the executive function evaluation questionnaire was used through the BRIEF behavior. Among the results, the existence of failures of self-regulation at a behavioral, cognitive and emotional level was detected, detected in the executive functions of emotional control, working memory and monitoring mainly. Therefore, the need to stimulate adequate executive functioning and self-regulatory capacities in children with ADHD is considered imperative
Keywords: TDHA; self-regulation; executive functions